2021
DOI: 10.3389/fmicb.2021.631096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Citric Acid and Lactobacillus plantarum on Silage Quality and Bacterial Diversity of King Grass Silage

Abstract: To better understand the mechanism underlying the citric acid (CA)-regulated silage fermentation, we investigated the bacterial community and fermentation quality of king grass (KG) ensiled without (CK) or with Lactobacillus plantarum (L), CA and the combination of L and CA (CAL). The bacterial community was characterized by using the 16Sr DNA sequencing technology. The L and CA treatments altered the silage bacterial community of KG, showing reduced bacterial diversity, while the abundance of desirable genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 46 publications
12
50
1
Order By: Relevance
“…Bacterial communities were altered by silage additives, whereas Firmicutes and Proteobacteria were always the dominant phyla. Results were consistent with those reported by Wang et al (2021) ; Zhang et al (2021) , and Zi et al (2021) . Almost all LAB belong to Firmicutes , which are involved in the degradation of biomacromolecules and secretes various lipases, cellulases, and proteases ( Yuan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bacterial communities were altered by silage additives, whereas Firmicutes and Proteobacteria were always the dominant phyla. Results were consistent with those reported by Wang et al (2021) ; Zhang et al (2021) , and Zi et al (2021) . Almost all LAB belong to Firmicutes , which are involved in the degradation of biomacromolecules and secretes various lipases, cellulases, and proteases ( Yuan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…After isolation, the concentration and quality of DNA samples were determined using the NanoDrop2000 Spectrophotometer (Thermo, United States). The Pyrobest DNA Polymerase (TaKaRa, DR500A) was adopted for the amplification of 16S rRNA V3–V4 regions of genomic DNA, and primer pairs were designed as 338F (5′-ACTCCTACGGGAGGCA GCA-3′) and 806R (5′-GACTACHVGGGTATCTAATCC-3′) in accordance with the method of Zi et al (2021) . The quality control and purification of PCR products were subsequently performed after amplification via the PicoGreen dsDNA Assay Kit (Invitrogen, Carlsbad, CA, United States) and Agencourt AMPure Beads (Beckman Coulter, Indianapolis, IN, United States).…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study showed that the addition of malic acid remarkably reduced the five α-diversity indices. Similarly, Zi et al found that silage king grass silage treated with citric acid had a lower OTU, Chao1 index, ACE index, and Shannon index, possibly because the addition of organic acids inhibits the growth of harmful bacteria [ 49 ]. The result of β-diversity reflected the distinction of the bacterial community in each individual or treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that LAB regularly relate to silage fermentation belong to the genera Enterococcus , Lactobacillus, Lactococcus, Leuconostoc, Pediococcus, Streptococcus , and Weissella ( Pang et al, 2011 ; Ni et al, 2018 ; Yang et al, 2019 ). The quality of silage mainly depends on the composition and abundance of microbial communities during ensiling ( Kung et al, 2018 ; Zi et al, 2021a ). Whole-plant maize silage has a better absorption rate and higher nutritional value than other silages, and is the most common feed for ruminants worldwide ( Khan et al, 2015 ; Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%